Asymptomatic neonatal colonisation by Clostridium difficile. Issue 5 (May 1984) - Bolton, R P; Tait, S K; Dear, P R; Losowsky, M S
Abstract : In a prospective survey of infants born in a single maternity unit, asymptomatic faecal colonisation by Clostridium difficile occurred in 31 (47%) of 66 babies who provided a faecal sample during week one of life and at age 14 and 28 days, and in 46 (30.7%) of the total of 150 babies for whom at least one faecal sample was obtained during the month of study. There was no evidence for acquisition of the organism from the mother during delivery and colonisation was unrelated to the means of delivery, infant sex, means of feeding, duration of hospital stay, or antibiotic treatment. New colonisation occurred throughout the month of the study and further evidence for environmental acquisition was obtained by the finding of a similar strain of C difficile in 7 babies from one ward together with positive environmental cultures. Colonisation was frequently transient and occasionally intermittent; most infants kept the same strain during their period of carriage. Twenty two (47.8%) babies colonised by C difficile had low titres of cytopathic faecal toxin but none had symptomatic diarrhoea or features of necrotizing enterocolitis. The in vitro toxigenic potential of 57 toxigenic isolates from 36 babies was low and 12 babies carried non-toxigenic strains. Transient colonisation by C difficile in early life is almost certainly more common than is generally recognized and the neonate provides an important reservoir of potential infection.